VIRTUAL SCREENING CAMPAIGNS ON ISOFLAVONES TO DISCOVER POTENT CYCLOOXYGENASE-2 INHIBITORS - Enade Perdana Istyastono (Jurnal Farmasi Sains dan Komunitas (Journal of Pharmaceutical Sciences and Community), 2017)
By employing recently published structure-based virtual screening (SBVS) to identify potent cyclooxygenase-2 (COX-2) inhibitors, all isoflavones collected by ZINC15 database were virtually screened. There were 3371 isoflavones in ZINC15 database and 1356 compounds out of them met the Lipinskis rule of 5. Notably, only 3 isoflavones out of those 1356 compounds were identified as potent COX-2 inhibitors.